The Impact of Underage Marriages on Family Welfare - Yusma Natasya Perdana; Abidin Abidin; Kamaruddin Kamaruddin (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2021)
This study examines the Impact of underage marriages on household welfare. The phenomenon of early marriage in Indonesia has attracted attention from scholars and practitioners. This study employed a qualitative method. The data were collected through direct observation, in-depth-interviews, and written document analysis. Data analysis was conducted through reduction techniques, data presentation, data verification, and conclusion drawing. The results of this study showed that the level of well-being of early marriage were included in the category below the establishment line of life both financially and spiritually. Factors causing changes in welfare include mindset, mental, and spiritual which is immature in family management causing a loss of the real purpose of building well-being and happiness families. The implication of this study was seen from Islamic law. Even though under ages marriage is legal in Islamic law perspective, but the marriage is not legal from government las perspectives. Underage marriage caused negative impact of family wel-being and happiness.